Shaping 3D root system architecture - Morris, Emily C.; Griffiths, Marcus; Golebiowska, Agata; Mairhofer, Stefan; Burr-Hersey, Jasmine; Goh, Tatsuaki; von Wangenheim, Daniel; Atkinson, Brian; Sturrock, Craig J.; Lynch, Jonathan P.; Vissenberg, Kris; Ritz, Karl; et al. (Elsevier (Cell Press), 2017)
Plants are sessile organisms rooted in one place. The soil resources that plants require are often distributed in a highly heterogeneous pattern. To aid foraging, plants have evolved roots whose growth and development are highly responsive to soil signals. As a result, 3D root architecture is shaped by myriad environmental signals to ensure resource capture is optimised and unfavourable environments are avoided. The first signals sensed by newly germinating seeds — gravity and light — direct root growth into the soil to aid seedling establishment. Heterogeneous soil resources, such as water, nitrogen and phosphate, also act as signals that shape 3D root growth to optimise uptake. Root architecture is also modified through biotic interactions that include soil fungi and neighbouring plants. This developmental plasticity results in a ‘custom-made’ 3D root system that is best adapted to forage for resources in each soil environment that a plant colonises.